PTU-199 A regional assessment of perineal wound complications after abdomino-perineal excision of the rectum. (22nd June 2015) - Sengupta, N; Tankel, J; Panagiotopoulou, I; Pournaras, D; Pilgrim, S; Challand, C; Keeling, N; Aryal, K; Lal, R; Brown, K; Obichere, M; Gurjar, S; et al.
Abstract : Introduction: Perineal wound complications following abdomino-perineal excision of the rectum (APER) are an important cause of morbidity in the treatment of low rectal cancers. Complications result in prolonged hospital stay, hospital readmission and higher medical expenditure. Our primary aim was to describe the short and long-term outcomes of the perineal wound and factors affecting wound healing after APER. Method: We performed a retrospective case note review of consecutive patients who underwent APER between January 2002 and January 2012 in three centres in the East of England. Demographic data and factors affecting perineal wound healing were analysed. Results: 242 patients (155 male, 76 female; median age 70 years) underwent APER. The median time to perineal wound healing was 2 months (range 1–37 months) with a minor perineal complication rate of 23.6% and major perineal complication rate of 22.7%. Perineal wound healing was significantly adversely impacted by use of the lithotomy operative position (p = 0.000), a positive circumferential resection (CRM) margin (p = 0.006), adverse tumour grade (p = 0.003) and lymph node (LN) positivity (p = 0.002). Patient factors (immunosuppression, diabetes mellitus and smoking) or preoperative treatment modalities (neoadjuvant chemoradiotherapy) were not statistically significant. Conclusion: Poor perineal wound healing after APER was associated with lithotomy patient positioning, CRM positivity and tumour grade. Disclosure of interest: None Declared.